2021
DOI: 10.3389/fonc.2021.688087
|View full text |Cite
|
Sign up to set email alerts
|

Two-Trait Predictor of Venous Invasion on Contrast-Enhanced CT as a Preoperative Predictor of Outcomes for Early-Stage Hepatocellular Carcinoma After Hepatectomy

Abstract: ObjectivesThis study aimed to assess the effectiveness of the two-trait predictor of venous invasion (TTPVI) on contrast-enhanced computed tomography (CECT) for the preoperative prediction of clinical outcomes in patients with early-stage hepatocellular carcinoma (HCC) after hepatectomy.MethodsThis retrospective study included 280 patients with surgically resected HCC who underwent preoperative CECT between 2012 and 2013. CT imaging features of HCC were assessed, and univariate and multivariate Cox regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“… 14 As for TTPVI, in the original study by Renzulli et al, 57.8% of the HCC patients undergoing hepatic resection were detected with TTPVI positive. 15 Li et al detected TTPVI in 44.3%, 16 whereas Zhang et al detected in 83% 42 of their study patients, suggesting TTPVI assessment to be more variable than RVI. However, in all studies, TTPVI was found to be highly predictive of MVI, showing a strong correlation with poor survival, which is in line with our findings for the TCGA-LIHC and iBT cohort.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“… 14 As for TTPVI, in the original study by Renzulli et al, 57.8% of the HCC patients undergoing hepatic resection were detected with TTPVI positive. 15 Li et al detected TTPVI in 44.3%, 16 whereas Zhang et al detected in 83% 42 of their study patients, suggesting TTPVI assessment to be more variable than RVI. However, in all studies, TTPVI was found to be highly predictive of MVI, showing a strong correlation with poor survival, which is in line with our findings for the TCGA-LIHC and iBT cohort.…”
Section: Discussionmentioning
confidence: 75%
“… 35 Both have been repeatedly validated by rad-path analyses in previous studies to facilitate their clinical application without the need for additional tissue biopsies. 16 , 17 Since these imaging biomarkers are derived from genomic analyses, previous studies indicated that they could represent a more fundamental phenotype of aggressive disease than MVI itself. 12 , 13 Specifically, Banerjee et al showed that RVI was predictive of OS and recurrence-free survival, whereas histological MVI was not.…”
Section: Discussionmentioning
confidence: 99%
“…The 1-, 2-, and 3-year RFS rates in the TTPVI-present group were 54.84%, 37.52%, and 33.67%, and those in the TTPVI-absent group were 81.08%, 69.99%, and 65.54%, respectively (p < 0.001). The 1-, 3-, and 5-year OS rates in the TTPVI-present group were 88.50%, 66.39%, and 57.32%, and those in the TTPVI-absent group were 95.92%, 89.57%, and 83.05%, respectively (p < 0.001) [44].…”
Section: Intratumoral Arteries and Enhancement Patternmentioning
confidence: 87%
“…In their study based on CECT imaging prior to liver resection, Zhao et al reported that the presence of intratumoral arteries in the arterial phase (p < 0.001), non-nodule type (p < 0.001), peritumoral enhancement in the arterial phase (p < 0.001), and absence of a radiographic tumor capsule (p < 0.001) were strongly associated with MVI [43]. Li et al investigated the relationship between the presence of a two-trait predictor of venous invasion (TTPVI) on preoperative imaging and postoperative prognosis [44]. The presence of internal arteries in the arterial phase and hypoattenuating halos in the portal venous or delayed phases is defined as TTPVI, and has been reported to correlate with specific HCC molecular profiles derived from microscopic venous invasion gene profiles related to cell proliferation, angiogenesis, and MVI [45].…”
Section: Intratumoral Arteries and Enhancement Patternmentioning
confidence: 99%
“…Dynamic contrast-enhanced computed tomography (CT) or MRI are the preferred imaging examination methods for HCC definitive diagnosis, and are routinely performed preoperatively 17 . Imaging features, such as internal arteries (IA), two-trait predictor of venous invasion (TTPVI), and incomplete capsule, can preoperatively and noninvasively predict MVI or survival outcomes 18 22 . Therefore, we hypothesized that imaging may help identify patients who will benefit from PA-TACE.…”
Section: Introductionmentioning
confidence: 99%